2008
DOI: 10.1139/z08-085
|View full text |Cite
|
Sign up to set email alerts
|

Strain-specific alteration of zebrafish feeding behavior in response to aversive stimuli

Abstract: Behavioral management of risk, in which organisms must balance the requirements of obtaining food resources with the risk of predation, has been of considerable interest to ethologists for many years. Although numerous experiments have shown that animals alter their foraging behavior depending on the levels of perceived risk and demand for nutrients, few have considered the role of genetic variation in the trade-off between these variables. We performed a study of four zebrafish (Danio rerio (Hamilton, 1822)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 53 publications
4
38
0
Order By: Relevance
“…Alternatively, the intermittent sounds may have reduced the focus of the fish on foraging opportunities as they could be more aversive and may be perceived as indicating increased predation risk. Oswald and Robison (2008) recently showed that aversive stimuli of a mechanical, visual and chemical nature slow down foraging in zebrafish, which may also be true for acoustic stimuli depending on the sound level as has also been shown for European minnows, which slow down their activities dramatically under experimental sound exposure (Voellmy et al, 2014).…”
Section: Impact Of Sound On Foraging Fishmentioning
confidence: 75%
“…Alternatively, the intermittent sounds may have reduced the focus of the fish on foraging opportunities as they could be more aversive and may be perceived as indicating increased predation risk. Oswald and Robison (2008) recently showed that aversive stimuli of a mechanical, visual and chemical nature slow down foraging in zebrafish, which may also be true for acoustic stimuli depending on the sound level as has also been shown for European minnows, which slow down their activities dramatically under experimental sound exposure (Voellmy et al, 2014).…”
Section: Impact Of Sound On Foraging Fishmentioning
confidence: 75%
“…This can be seen most clearly in the case of antipredator behaviour, which tends to be less well developed in farmed fish than in fish of wild origin (Chapter 8). For example, domesticated zebrafish (Danio rerio) show reduced shoaling, weaker startle responses and weaker suppression of feeding response under predation risk than do laboratory-reared undomesticated fish (Wright et al 2006;Oswald & Robison 2008). As a second example, domesticated brown trout (Salmo trutta) are slower to react to a simulated predatory attack than are hatchery-reared wild fish (Petersson & Jarvi 2006).…”
Section: Effects Of Genes On Behaviourmentioning
confidence: 99%
“…The place preference test is based on captive zebrafish feeding behavior. In captivity, zebrafish respond to an approaching person by swimming to the front and top of their tank and waiting under the feeding hole (Oswald and Robison, 2008; Benner et al, 2010). We took advantage of this behavior to test whether fish could respond to visual stimulus.…”
Section: Methodsmentioning
confidence: 99%